Are Academics Satisfied with the Measurement and Evaluation Practices Applied During Emergency Remote Teaching due to COVID-19? - Özdemir, Hasan Fehmi; Toraman, Çetin; Korkmaz, Güneş (Universitepark, 2022)
Background/purpose -The aim of this research is to examine the meanings through metaphors that academics derive from their experiences regarding the measurement and evaluation practices when emergency remote teaching was conducted due to the COVID-19 pandemic, to identify the problems they experienced with the measurement and evaluation practices, and to present their solution recommendations. Materials/methods -The study was structured as a qualitative research. The problems experienced by academics in measurement and evaluation practices, together with their solution suggestions were examined according to the "basic qualitative research" pattern. On the other hand, the "phenomenological qualitative research" design was used since the meanings attributed to the measurement and evaluation practice experiences were examined through metaphors. The participants of the study were 2,321 academics teaching at state and private universities in Turkey. Results - The findings reveal that most of the problems experienced were related to "cheating, test security, fair exam environment, plagiarism, inability to measure whether learning objectives had been achieved, inappropriate online measurement and evaluation methods, lack of quality in assessment practices, and technical issues regarding learning management systems." Conclusion - The solutions proposed by the participant academics were the use of alternative assessment methods, conducting face-to-face rather than online exams, asking different questions for each student by mixing up the questions in the exam, and using webcams for online exam invigilation. Metaphors attributed to the measurement and evaluation practices were grouped under three categories; as positive metaphors (e.g., lighthouse, life buoy), negative metaphors (e.g., hallucination, digging a well with a needle), and metaphors implying that such practices played a key role (e.g., water in desert, surgery) in emergency. © © 2022 by the author(s). This work is licensed under a Creative Commons Attribution-Noncommercial 4.0 International License (CC-BY-4.0), where it is permissible to download and share the work provided it is properly cited.
Keywords: academics; Emergency remote teaching; measurement and evaluation; metaphors; qualitative study